Entrepreneurial Ideas, Business Canvas Model and Digital Marketing for Young Farmers of Tangkoro Village in Utilizing Cocoa Waste - Sumangelipu, Andi; Wahda, Muhammad Aksha; Fadhillah, Prayudhi (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
In Tangkoro Village, Pitumpanua District, Wajo Regency, 22.54% of the total population of 1,167 people work as farmers or plantation owners. Their main crop is cocoa, in addition to other commodities such as cloves, pepper, and fruit. Farmers cannot process their own cocoa harvest because it has been purchased by PT Cargill. Therefore, to earn additional income, they can only utilize cocoa waste. This community service aims to help farmers identify entrepreneurial ideas for utilizing cocoa waste into finished products and marketing them digitally. This empowerment is carried out through lectures (counseling) and simulations (training) to increase farmers' knowledge in finding business ideas using the Business Model Canvas in utilizing cocoa waste and marketing it digitally. The results of this empowerment study, based on pretest and posttest results, can improve farmers' ability to find business ideas for utilizing cocoa waste and utilizing digital marketing.